2018
DOI: 10.1155/2018/9509356
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Liver Abscess with No Predisposing Risk Factors

Abstract: Pyogenic liver abscesses (PLA) are an uncommon cause of hospitalization in the United States. The majority of such cases are polymicrobial and are most commonly caused by seeding of infection from the biliary system. PLA is frequently associated with specific comorbidities such as diabetes mellitus, history of liver transplant, underlying hepatobiliary, or pancreatic disease. Herein, we describe a 47-year-old healthy male with no known risk factors associated with PLA who presented to the hospital with acute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Our study is in coherence with some studies. [ 3 9 ] But, this is in contrast to several studies which found a mean age in sixth and seventh decades. [ 4 10 11 12 13 ] Most of the studies found both male and female as patients and male outnumbered over female.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our study is in coherence with some studies. [ 3 9 ] But, this is in contrast to several studies which found a mean age in sixth and seventh decades. [ 4 10 11 12 13 ] Most of the studies found both male and female as patients and male outnumbered over female.…”
Section: Discussionmentioning
confidence: 66%
“…PLA accounts for 48% of visceral abscess. [ 9 ] It has still a great impact on health care facility and delay or improper management may lead to significant loss of life. In our study, the mean age of patients was 37.9 years with maximum cases (44%) between 31 and 40 years age group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its incidence varies between 2.3 and 17.59 per 100 000 inhabitants per year,1–3 and in hospitalised patients, it is 8–22 cases per 100 000 hospital admissions 4. Usually occurs in Caucasian men between 50 and 60 years old 5.…”
Section: Pyogenic Liver Abscessmentioning
confidence: 99%